PENGEMBANGAN MEDIA PEMBELAJARAN BOOKLET ARLANSIA PADA MATA PELAJARAN PPKn UNTUK MENINGKATKAN HASIL BELAJAR KELAS III SEKOLAH DASAR - Silawati, Silawati; Hakim, Lukman; Aryaningrum, Kiki (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to produce an Arlansia booklet media for PPKn learning that is valid, practical and effective. The type of research used is Research and Development with the ADDIE model which consists of five stages, namely: 1) Analyze, needs analysis and curriculum analysis, 2) Design, designing and selecting the appearance of the Arlansia PPKn learning booklet media. 3) Development, validation of products that have been developed. 4) Implementation, the application of the product to determine the practicality of the PPKn learning Arlansia booklet, and 5) Evaluation, the evaluation of the PPKn learning Arlansia booklet to determine the advantages and disadvantages of developing the PPKn learning Arlansia booklet media. Data collection techniques are in the form of questionnaires to determine the validity and practicality of the media, validation questionnaires, student response questionnaires and teacher response questionnaires, as well as tests to determine the effectiveness of the media in the form of 10 multiple choice questions. The research results showed that the percentage value of media validation was 74%, material validation was 72% and language validation was 70% in the valid category, teacher response questionnaire results was 88%, individual trial student response questionnaires was 84%, group trial student response questionnaires small at 82% in the very practical category and effective questionnaire results at 91.6% in the very effective category. So it can be concluded that the development of arlansia booklet learning media at class III on PPKN subjects can be categorized as valid and practical for use in learning activities.